Artificial Intelligence in Arabic-English Literary Translation: Technological Innovations, Linguistic Accuracy, and Ethical Implications - Abdulmughni, Hameed Mohammed Abdulfatah (International Journal of Language and Literary Studies, 2025)
This research investigates the application of Artificial Intelligence (AI) in Arabic-English literary translation, examining the complex intersection of technological capabilities, linguistic challenges, and ethical considerations. The study employs a mixed-methods approach combining computational analysis of translator-AI interactions, comparative assessment of machine and human translations, and qualitative interviews with professional translators and literary experts. Analysis of a diverse corpus of Arabic literary texts reveals that while neural machine translation (NMT) systems have made significant advances in handling basic linguistic structures, they continue to struggle with the cultural nuances, stylistic features, and contextual depth that characterize literary texts. The research identifies specific challenges in translating Arabic literary devices, metaphorical expressions, and culturally embedded concepts, while proposing targeted enhancements to existing NMT architectures. These include the development of specialized cultural knowledge modules, improved handling of Arabic morphological complexity, and hybrid human-AI workflows that leverage the strengths of both machine efficiency and human cultural interpretation. The study also addresses the ethical implications of AI integration in literary translation, examining issues of authorial voice preservation, translator agency, and cultural representation. The findings suggest that while AI can serve as a valuable assistive tool in the translation process, the translation of literary texts continues to require human oversight to ensure cultural authenticity, stylistic integrity, and ethical representation. This research contributes to the evolving understanding of AI's role in translation studies and offers practical frameworks for the responsible integration of technology in preserving the art of literary translation.